Chemical Characterization and Bioactive Properties of Wine Lees and Diatomaceous Earth towards the Valorization of Underexploited Residues as Potential Cosmeceuticals - Cristina N. Duarte; Oludemi Taofiq; Maria Inês Dias; Sandrina A. Heleno; Celestino Santos-Buelga; Lillian Barros; Joana S. Amaral (Cosmetics, 2023)
Annually, wine production is responsible for generating large quantities of residues, which are frequently disposed of and not valorized. So far, different studies have been conducted on grape pomace, yet less attention has been paid to other residues, such as wine lees and diatomaceous earth used in wine filtration. In this context, this study aimed to evaluate and compare the phenolic profile of these underexploited winemaking residues and assess their biological potential based on their antioxidant, antimicrobial, cytotoxic, and anti-aging activities (inhibition of tyrosinase and collagenase). Twenty-nine phenolic compounds, including twelve anthocyanins, were tentatively identified in the residues, with red grape pomace showing the highest diversity of compounds. The diatomaceous earth presented the highest content of non-anthocyanin phenolic compounds, being particularly rich in flavan-3-ols and myricetin-O-hexoside, and also presenting two anthocyanins. This sample also showed a high antioxidant activity, evidencing the best result in the reducing power assay. The red wine lees extract, despite showing a low content of phenolic compounds and less antioxidant activity, presented the highest inhibition capacity of bacteria growth. The extracts did not exhibit cytotoxicity against keratinocyte (up to 400 μg/mL) and fibroblast (up to 100 μg/mL) skin cell lines. However, the capacity of inhibiting tyrosinase and collagenase was low for the lees and diatomaceous earth, contrary to the grape pomace, seeds, and skins extracts that showed promising results, evidencing its potential as a cosmeceutical. Overall, this study highlights for the first time the potential of diatomaceous earth, an underexploited winemaking waste, in the obtention of added-value extracts and/or ingredients for cosmetic industry.